从美学视野看现代革命京剧 ：“样板戏” 的继承、借鉴与突破 = An aesthetics view on the succession and breakthrough of the revolutionary model opera - 吴坤容 Goh, Kun Rong (2013)
现代革命京剧，又称 “样板戏”， 是中国“文革”时期，在革命文坛创作中重要的文艺组成成份。由于 “样板戏” 产生于一个复杂的社会文化背景，因此强烈的体现出了当时文革时代的精神，也包含了当时重要的政治思潮和文化课题。 对于 “样板戏”的评价，人们首先注意到的就是它所承载的政治力量和意识形态功能。经过学界多年的争论，母庸置疑 “样板戏” 是属政治性极强的文化作品, 但是它所承载的艺术价值却不应该被政治的衣裳遮盖，纯粹背负着政治色彩的枷锁而已。 因此，本文将剥开 “样板戏” 的政治意识形态，从美学视野对 “八大革命样板戏” 的艺术价值和表现手法做出研究分析， 并且从多个艺术元素中探讨其作品的继承、借鉴、突破和影响。从而揭示这个极左派主导的文艺作品作为历史文化的艺术产物是否值得更多的学者和大众去认同它独特的艺术价值？Revolutionary Opera, also known as the Model Opera, is a significant and major component that best unified the literature and arts progression of China during the Cultural Revolution. The birth of the Model Opera collides with its complicated social background, therefore strongly showcases the spirit of Cultural Revolution, thus capturing the political ideology and cultural aspects of the era. As such, Model Opera had been considered widely by researchers as a dictated performance that was planned and engineered with strong political objective, thus uses it as a powerful weapon to emphasize the victory of the People's Liberation Party. It was also due to this strong political ideology that resulted in the denial of the artistic achievement of the Model Opera. This dissertation aims to provide an aesthetical overview of the Eight Revolutionary Model Opera through the analysis of the various thematic components that buildup the succession and breakthrough of the Model Opera. Upon that, the research findings hope to provide a justified status for the artistic values of the Model Opera.